Technical diversification, body composition and somatotype of both heavy and light Polish ju-jitsukas of high level - Sterkowicz-Przybycien, K. (Science & Sports, 2010)
Ju-jitsu is a combat sport that combines techniques of both karate and judo. Tournaments are organized in six weight categories. Identification and classification of somatic build in top contestants practicing ju-jitsu is important for establishment of a model of champion for this discipline of professional sport. There is also no evaluation of the relationships between the sports level and technical and tactical preparation of the contestants.